G09 Do Parents Agree with Examiners When Rating Student Competence in Exams?. (4th June 2013) - Feyereislova, S; Nathan, D
Abstract : Aims: To compare examiner and parental ratings of students undertaking a summative clinical assessment of history-taking and examination skills in a ward based setting. Methods: Parents of patients participating in the 4th year medical students' ward based assessments were asked for feedback and an evaluation of student performance through validated questionnaire. Students completed a paediatric history and head to toe examination of a child admitted to an acute medical ward within a defined time. The clinical case was presented to examiners (experienced clinicians – paediatric consultants and/or senior Trainees). Examiners ratings were based on student competence in presentation of medical history and examination findings, with observed examination technique and their communication skills during a predetermined clinical role play situation. The latter grading mirrored an RCPCH scoring system. Parental ratings were based on the Interpersonal Skills Rating Scale which encompassed their impression of the student's interaction with them and their child. The data was collected in the 2011–2012 academic year. We then correlated aggregated parental scores with examiner rating of the same student. Results: In total, 129 parent evaluations were obtained for 129 students. One hundred and nine parental feedback forms were fully completed and correlated with examiners' scores of matching students. The correlation coefficient for the total scores given by parents and examiners was –0.04, with intercept at score 22 and the slope of –0.02. The average score given by parents is 22 (range 16–24). The average score given by examiners is 18 (range 7–24). Conclusion: In general, parental rating does not correlate with clinical examiner rating. Parental ratings of students demonstrate less variation compared to examiner rating scores. Notably, low scoring students were not necessarily considered by parents as underperforming, suggesting students' good communication and interpersonal skills irrespective of technical knowledge.